Agriculture at the doors of the city: leaseholders, small owners and big farmers (Quinto Sol, 2013)
This piece of work forms parte of a major researchbased on the analysis of process of structuring and development  of the most dynamic periurban settlements in Buenos Aires surroundings between the early 19th century and the decade of 1870. Dealing specifically with Flores District- a tiny universe of small farms orchads specialized in the cereal and horticultural activity in the public market- we seek to articulate the general characteristics of the process of settlement in Western Buenos Aires, with the dinamics linked to the productive use of agricultural land that was closer to the area, and executions of wills and tax lists make up the documentary basis for our study.
Keywords: Periurban space; population; agricultura; market